Synthesis and characterisation of thermally stable ka[cu2(p-oc6h4coo)a(ch3(ch2)ncoo)4-a] and [cu2(p-h3nc6h4coo)a(ch3(ch2)ncoo)4-a]xa and their reactions with selected ketones / Zaimatul ‘Azian Kamarazaman - Kamarazaman, Zaimatul ‘Azian (2012)
This research focussed on the development of the synthetic methods and characterisation (structural, thermal, magnetic and redox properties) of two types of ionic copper(II) mixed-carboxylates: (a) Ka[Cu2(p-OC6H4COO)a(CH3(CH2)nCOO)4-a], and (b) [Cu2(p-H3NC6H4COO)a(CH3(CH2)14COO)4-a]Xa, where a = 1, 2; n = 14, 10, 8, and 6; X = Cl, CH3COO and CF3SO3. These complexes were designed to be thermally stable and magnetic metallomesogens and/or metal-containing ionic liquids. The synthetic methods used to prepare these complexes were one-pot reaction, ligand-exchange reaction, and acid-carbonate-base reaction. A total of twelve (12) complexes were successfully prepared and fully characterised (Table 1). Table 1 The structural formulas of the complexes Complex Structural formula 1 K2[Cu2(p-OC6H4COO)2(CH3(CH2)14COO)2(p-HOC6H4COOH)2].2H2O 2 [Cu2(p-HOC6H4COO)2(CH3(CH2)14COO)2(CH3(CH2)14COOH)(H2O)]. CH3CH2OH 3 [Cu2(p-H2NC6H4COO)2(CH3(CH2)14COO)2].2H2O 4 K[Cu2(p-OC6H4COO)(CH3(CH2)14COO)3] 5 [Cu2(p-HOC6H4COO)(CH3(CH2)14COO)3(CH3CH2OH)2] 6 [Cu2(p-HOC6H4COO)(CH3(CH2)10COO)3].H2O 7 [Cu2(p-HOC6H4COO)(CH3(CH2)8COO)3].CH3CH2OH 8 [Cu2(p-HOC6H4COO)(CH3(CH2)6COO)3(CH3(CH2)6COOH) (CH3CH2OH)].H2O 9 [Cu2(CH3(CH2)14COO)2(OH)2(H2O)4].2C2H5OH 10 K2[Cu2(CH3(CH2)10COO)2(OH)4] 11 K2[Cu2(CH3(CH2)8COO)2(OH)4] 12 K2[Cu2(CH3(CH2)6COO)2(OH)4] iv The structural formulas of these complexes were deduced from elemental analyses, FTIR and UV-vis spectroscopies. The thermal properties were determined by TGA and DSC, while the mesomorphic properties were determined by OPM. The magnetic properties were determined by Gouy method using a magnetic susceptibility balance, and the redox properties by cyclic voltammetry. Additionally, GCMS was used to analyze the products formed from the carbon-carbon bond-forming reaction of methyl carbonyl (3,3-dimethyl-2-butanone). The structure of most of the complexes were dimeric paddle-wheel with either square planar or square pyramidal geometry at copper(II) centres. Complex 1 had the highest thermal stability (Tdec = 424oC) compared to the other complexes (Tdec = 200oC – 250oC). Additionally, the complexes with a higher ratio of the alkylcarboxylate ligands (aromatic: aliphatic = 1:3) were more thermally stable; the stability increases with increasing alkyl chain length. However, the opposite trend was noted for the melting temperatures: complexes with a higher ratio of the alkylcarboxylate ligands had a lower melting point. Six of the complexes (Complex 2, Complexes 5 - 9) exhibited metallomesogenic properties. However, the type of mesophase cannot be deduced with certainty from OPM. All complexes were magnetic at room-temperature. Except for Complex 1 which showed a weak ferromagnetic interaction (μeff = 3.12 B.M.; 2J = 60 cm-1), the other complexes had magnetism (μeff = 1.87 B.M. - 2.62 B.M.) which were lower than the spin-only value for two unpaired electrons (μeff = 2.83 B.M.), with variable strength of antiferromagnetic interaction (2J = -78 cm-1 to -346 cm-1). The complexes with a higher ratio of the alkylcarboxylate ligands have a stronger antiferromagnetic interaction. However, the difference in the chain length did not have much effect on the magnetic interaction. v All of the complexes were redox-active and showed step-wise quasi-reversible electrochemical reaction. The initial reduction potentials were in the range of 0.07-0.30 V. Both Complex 1 and Complex 4 ‘catalysed’ the carbon-carbon bond-forming reaction of 3,3-dimethyl-2-butanone. Complex 4 seemed to be a better ‘catalyst’ as the products formed were in higher purity and amount. The findings of this research were published in one (1) ISI journal and presented either orally or as poster at three (3) national and four (4) international conferences and seminars (Appendix 1).